Comprehensively analysis of hot electron transport in as-grown and thermally annealed n-type modulation-doped Al0.15Ga0.85As/GaAs0.96Bi0.4 quantum well structure. (February 2023) - Donmez, Omer; Aydın, Mustafa; Mutlu, Selman; Puustinen, Janne; Hilska, Joonas; Guina, Mircea; Erol, Ayse
Abstract: We report experimental and analytical results on hot electron transport in as-grown and thermally annealed n-type modulation-doped Al0.15 Ga0.85 As/GaAs0.96 Bi0.4 quantum well (QW) structures at room temperature. The drift mobility of as-grown and thermally annealed samples is 2265 and 1414 cm 2 /Vs at a low electric field region, respectively. The lower electric field electron mobility for the thermally annealed sample is due to the increased 2D electron density following the annealing process. The drift velocity ( v d r i f t ) of the as-grown sample tends to saturate at 6.1 × 10 6  cm/s, contrary to the thermally annealed sample, for which no saturation is observed. The v d r i f t of the annealed sample is also lower due to the higher 2D electron density caused by annealing. Analyzing the experimental results concerning the theoretical model reveals that i) hot electron transport occurs in parallel mode due to the presence of electrons in both Al0.15 Ga0.85 As (barrier) and QW layers, ii) hot electrons transferred from QW to the barrier layer via so-called real space transfer (RST) mechanism is suppressed at higher electric fields even though the lower energy barrier between the barrier and QW layers, and iii) transfer of electrons from QW ( Γ -valley) to the nearest L-valley, inter-valley transfer (IVT), dominates on the hot electron transfer at higher electric fields even with a higher energy barrier.